2011
DOI: 10.1523/jneurosci.4936-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Magnetic Resonance Imaging Detection of Cerebral Amyloid Angiopathy-Related Microvascular Alterations Using Superparamagnetic Iron Oxide Particles in APP Transgenic Mouse Models of Alzheimer's Disease: Application to Passive Aβ Immunotherapy

Abstract: Cerebral amyloid angiopathy (CAA) is a common feature of Alzheimer's disease (AD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 39 publications
8
42
1
Order By: Relevance
“…We found no accumulation of the SPIONs in blood vessels. This is consistent with the small size of the SPIONs used and the fact that Beckmann et al [75] have found no detectable cerebral amyloid angiopathy or MRI-detectable lesions in singly-transgenic AβPP mice for mice less than 15 months of age. Our mice were only 14 months old when killed for this study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found no accumulation of the SPIONs in blood vessels. This is consistent with the small size of the SPIONs used and the fact that Beckmann et al [75] have found no detectable cerebral amyloid angiopathy or MRI-detectable lesions in singly-transgenic AβPP mice for mice less than 15 months of age. Our mice were only 14 months old when killed for this study.…”
Section: Discussionsupporting
confidence: 83%
“…1H). We were initially surprised by this result because amyloid plaques are known to contain iron [74], but several investigators have found [21, 31, 74, 75] that simple Perl’s staining, without DAB enhancement, does not reveal the small amount of iron present in the cortical plaques from transgenic PS1/AβPP mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, the detection of CAA-related alterations in the microvasculature remains crucial for the evaluation of therapies. A previous study clearly showed that passive β-amyloid immunotherapy in APP23 mice amplified microhemorrhages throughout the entire brain 34 . In our study, we showed that high-resolution gre3D anatomical MRI at 7 T is sensitive enough for the detection of cerebral microhemorrhages without contrast agents.…”
Section: Discussionmentioning
confidence: 90%
“…For the above study, MNPs were injected i.v. to transgenic AD mice, after 24 h of administration these particles were taken up by macrophages and attenuation of MRI signals increased the detectability of the lesions in AD mice [53]. Detecting such events in vivo can facilitate understanding of the role of CAA in dementia development.…”
Section: Theranostic Approach Of Mnps For Neurodegenerative Diseasementioning
confidence: 99%